The role of internal control systems in supporting external auditors in providing reasonable assurance on financial statements - Adam Muhamad Satria; Lidya Primta Surbakti (PT WIM Solusi Prima, 2026)
This study aims to analyze the role of the internal control system in supporting external auditors in providing reasonable assurance regarding the fair presentation of financial statements. The reliability of financial statements is highly influenced by the effectiveness of the internal control system implemented by an entity, as such a system functions to minimize the risk of errors and fraud that may affect the quality of financial information. This study adopts a descriptive qualitative approach using a library research method. The findings indicate that an internal control system designed and implemented based on the COSO framework enhances the effectiveness of internal controls, improves the reliability of financial reporting, and reduces the risk of material misstatements. Furthermore, an effective internal audit function serves as a bridge between the internal control system and the external audit process. In accordance with International Standard on Auditing (ISA) 610, external auditors may rely on the work of internal auditors to modify the nature, timing, and extent of audit procedures, thereby improving audit efficiency without compromising the quality of audit evidence obtained. The study also reveals that effective internal controls are positively associated with the quality of external audit opinions. Companies with strong internal control systems are more likely to receive unmodified audit opinions, whereas deficiencies in internal controls increase the risk of material misstatements that may lead to modified audit opinions. Therefore, the relationship among internal control systems, internal audit, and external audit is synergistic in enhancing financial reporting quality, improving audit efficiency, and fostering the continuous improvement of internal control systems.